2020
DOI: 10.1108/ijm-12-2019-0555
|View full text |Cite
|
Sign up to set email alerts
|

There is a time and a place for work: comparative evaluation of flexible work arrangements in Canada

Abstract: PurposeUsing the Canadian General Social Survey of 2016, a large nationally representative dataset, the present paper compares different types of flexible work arrangements in their associations with employee wellbeing and organizational outcomes.Design/methodology/approachThe dataset contains 7,446 observations. Informed by the past scholarship, eight outcomes of job satisfaction, work-life balance satisfaction, organizational belonging, job motivation, perceived advancement prospects, perceived job security,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 55 publications
0
31
1
9
Order By: Relevance
“…Notably, home-based teleworking allowed employees to improve their work–life balance, although women and families with children did experience more conflicts (Rodríguez-Modroño & López-Igual, 2021). Dilmaghani (2021) reasoned that the positive associations between flexible working arrangements like telework and work–life balance satisfaction were stronger among men and women without children. They further identified that employees with both flextime and flexplace only experienced significantly higher job and work–life balance satisfaction than employees without any flexible work options (Dilmaghani, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, home-based teleworking allowed employees to improve their work–life balance, although women and families with children did experience more conflicts (Rodríguez-Modroño & López-Igual, 2021). Dilmaghani (2021) reasoned that the positive associations between flexible working arrangements like telework and work–life balance satisfaction were stronger among men and women without children. They further identified that employees with both flextime and flexplace only experienced significantly higher job and work–life balance satisfaction than employees without any flexible work options (Dilmaghani, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Social exchange theory states that employees are ready to offer their labor and loyalty in return for the economic and social benefits offered by the organization in the employee-employer relationship [ 43 ]. Social exchange theory proposes that flexible work arrangements will reciprocate the employer’s effort by generating a sense of gratitude in employees, demonstrating higher motivation and loyalty for their work [ 44 ]. The commitment-trust theory argues that when commitment and trust exist together, there will be increased efficiency, productivity and efficiency in the work environment [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to telework, a flexible schedule is a non‐negligible positive predictor of job satisfaction, for both men and women. Similarly contrasting patterns between telework and flexible schedule have been reported regarding work–life balance satisfaction (Dilmaghani, 2020). Finally, the ease of taking time off for family matters is a statistically significant and positive predictor of job satisfaction for both men and women, with similar coefficients.…”
Section: Resultsmentioning
confidence: 73%
“…Despite that, the evidence supporting the positive effects of flexible work arrangements on employee well‐being, especially their job satisfaction, is compelling (Golden & Veiga, 2005; Gajendran & Harrison, 2007; Chung & Van der Lippe, 2020). There are also growing evidence regarding the greater impact of flexibility on female satisfaction with work‐related outcomes (Okulicz‐Kozaryn & Golden, 2018; Dilmaghani, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%